The Correlation between EFL Students’ Vocabulary Mastery and Their Reading Ability - Shacitra Ayu Cleverisa; Sahiruddin Sahiruddin; Widya Caterine Perdhani (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2022)
This study examines the correlation between students’ vocabulary mastery and their reading ability. The purpose of the research is to know whether the correlation is evident between students' vocabulary mastery and their reading ability at the second semester of eight grade of SMPN 4 Pare in the academic year of 2020/2021. The researcher used a quantitative approach through correlational research. The researcher used correlational research design by vocabulary and reading tests to the second year students of SMPN 4 Pare. The researcher used a test that consists of 57 items as an instrument of this study. There were 34 students of the second year students of SMPN 4 Pare participating in this study. The study reveals that there is a strong significant correlation between students’ vocabulary mastery and their reading ability at r=.8769, p<.005. This study demonstrates that the vocabulary mastery is important for reading ability as vocabulary will enhance reading comprehension. Pedagogical implication of this study is discussed.